Influence of stirrup spacing on shear resistance and deformation of reinforced concrete beams - M S, Latha; M, Revanasiddappa; B M, Naveen Kumar (International Journal of Engineering and Technology, 2018)
An experimental investigation was carried out to study shear carrying capacity and ultimate flexural moment of reinforced cement concrete beam. Two series of simply supported beams were prepared by varying diameter and spacing of shear and flexural reinforcement. Beams of cross section 230 mm X 300 mm and length of 2000 mm. During testing, maximum load, first crack load, deflection of beams were recorded. Test results indicated that decreasing shear spacing and decreasing its diameter resulted in decrease in deflection of beam and increase in bending moment and shear force of beam.
Keywords: Deflection; Flexural; Moment; Shear; Stirrups.